Different types of emollient cream exhibit diverse physiological effects on the skin barrier in adults with atopic dermatitis - Danby, Simon G.; Andrew, Paul V.; Taylor, Rosie N.; Kay, Linda J.; Chittock, John; Pinnock, Abigail; Ulhaq, Intisar; Fasth, Anna; Carlander, Karin; Holm, Tina; Cork, Michael J. (Clinical and experimental dermatology, 2022)
Summary Background Eczema (atopic dermatitis; AD) is a very common itchy skin condition affecting 1 in 5 children and up to 1 in 10 adults worldwide. The skin of eczema sufferers is prone to redness, irritation and dryness because it does not form an effective barrier, i.e. the ability of the skin to stop irritants, allergens and microorganisms getting into the body. Skin barrier dysfunction is a hallmark of AD. The regular and liberal (600 g/week for an adult) use of emollients is recommended for all patients with eczema), even between episodes of itching and redness, to soften and soothe the skin. In England alone, almost 9 million prescriptions for emollient creams were issued in 2018, at a cost of over £50 million. Despite this widespread use, relatively little is known about how commonly prescribed emollient creams affect the skin's barrier, and thus the role of moisturizers in AD development and progression remains unclear. We set out to compare three different types of emollient cream and a no‐treatment control. Aim To compare the barrier‐strengthening properties of a new moisturizer containing urea and glycerol (urea–glycerol cream; UGC), with those of a glycerol‐containing moisturizer (glycerol cream; GC), a simple paraffin cream (PC) with no humectant, and a no‐treatment control (NTC). Methods This was an observer‐blinded prospective Phase 2 within‐subject multilateral single‐centre randomized controlled trial in adults with AD (Clinical Trials #NCT03901144). The intervention involved 4 weeks of treatment, twice daily, with the three products applied to one of four areas on the forearms the (the fourth area was the untreated control, randomized allocation). Skin properties [dryness, transepidermal water loss (TEWL), hydration and natural moisturizing factor (NMF) levels] were assessed before, during and after treatment to see what happened to the skin's barrier. The primary outcome was skin sensitivity to the irritant sodium lauryl sulfate (SLS) after treatment. We performed tests on the skin before and after treatment to see what happened to the skin's barrier. Results In total, 49 patients were randomized, completed treatment and included in the analysis. UGC significantly reduced the response to SLS as indicated by a reduction in TEWL compared with NTC (−9.0 g/m2/h; 95% CI −12.56 to −5.49), with PC (−9.0 g/m2/h; 95% CI −12.60 to −5.44) and with GC −4.2 g/m2/h; 95% CI 7.76 to −0.63). Skin moisturization improved at sites treated with UGC compared with NTC and PC, and this was accompanied by concordant changes in dryness and NMF levels. Subgroup analysis suggested FLG‐dependent enhancement of treatment effects. Conclusion The study showed that not all emollient creams for eczema are equal. The simple paraffin‐based emollient, which represents the most widely prescribed type of emollient cream in England, had no effect on the skin's barrier and reduced the skin's NMF. UGC markedly improved the skin's barrier and protected against irritation. GC performed better than PC, but not as well as UGC. UGC strengthened the skin barrier through a mechanism involving increased NMF levels in the skin, and imparted protection from SLS‐induced irritation. By helping correct a major pathophysiological process, UGC has the potential to improve the long‐term control of AD. The results show that different emollient creams have different effects on our skin, and only certain types have the ability to improve the skin's barrier and protect against irritants that trigger eczema. This study compares the barrier‐strengthening properties of a new moisturizer, containing urea and glycerol, to a glycerol‐containing moisturizer, a simple paraffin cream (no humectant), and no treatment. In contrast to the simple paraffin cream, the urea/glycerol cream strengthened the skin barrier through a mechanism involving increased natural moisturizing factor levels in the skin, and imparted protection from irritation. By helping correct a major pathophysiological process, the urea/glycerol cream has the potential to improve the long‐term control of atopic eczema.